THE IMPORTANCE OF NATIONAL SPIRITUAL VALUES IN THE DEVELOPMENT OF ENVIRONMENTAL LITERACY IN STUDENTS (Scientific journal of the Fergana State University, 2023)
The article deals with the importance of national spiritual values in the development of the concepts of the formation of ecological literacy in students and the observance of students to keep the environment clean, tidy, virgin.